Handling Covid-19 in Sampang: leadership and local elite public communication strategy - Hidayat, Endik; Susilo, Daniel; Garcia, Erica Monica A. (Jurnal Studi Komunikasi, 2021)
After the Covid-19 outbreak, the emergence of an economic recession is the impact of various policies to prevent the spread of the virus, such as the extreme lockdown policy to Large-Scale Social Restrictions. Sampang, a small regency in Madura Island, Indonesia, has successfully maintained the low case of Covid-19. This article elaborates on the success of the Sampang Regency in maintaining its green zone status. More specifically, what is the Sampang government's communication strategy during the Covid-19 pandemics. This article used a qualitative method with a case study approach in ten villages of Sampang with a Focus Group Discussion. The results show that the local elite's communication strategy in Sampang during the pandemic situation does not only physically come directly to the field or meet villagers but also virtually using mass media effective to maintain the low index Covid-19 transmission.